Telehealthcare initiatives usefulness among mental healthcare professionals in neuropsychiatric hospitals - Opaleye, Temitope Elizabeth; Owoeye, Isaiah Dada; Omitogun, Ezekiel Olusola; Olabisi, Oluwaseyi Isaiah (KHD-Production, 2025)
Telehealthcare use among mental health professionals will enhance professional healthcare services, but this development is slow and fraught with challenges in Nigeria's mental health services. This study explores the mental health professionals (MHP) perceived usefulness of Telehealthcare initiatives at Neuropsychiatric hospitals (NH) in Southwest Nigeria. The study followed a descriptive phenomenological approach. Semi-structured interviews were conducted face-to-face and telephonically with seven mental health professionals, including nurses, psychiatrists, pharmacists, clinical psychologists, social workers, and occupational therapists, who were purposely sampled from the NH in Southwest, guided by data saturation. The audio-recorded interviews were transcribed and inductively analyzed using descriptive phenomenological analysis with the aid of the ATLASti Version 9 program. The study was analyzed thematically. Two themes emerged: (1) Improved healthcare access and (2) Reduced stigmatization. The results of this study indicated that mental health professionals perceived that telehealthcare makes work faster and patients can access care easily; also, stigmatization of mental health patients is reduced as they are not seen physically attending Neuropsychiatric hospitals. Therefore, further studies are needed on the effectiveness of telehealthcare utilization among mental health patients. It is therefore recommended that there should be an increase in the provision of telehealthcare infrastructure and an increase in manpower to meet the needs of mental health seekers.